Multiple Shoot Bud Formation and Plantlet Regeneration from in vitro Cultured Pistacia vera Seeds: Short Communication (Biological Sciences - PJSIR, 2005)
Studies were carried out on the primordial initiation and development of shoot buds derived from pistachio (Pistacia vera) seedlings, cultured on MS medium with added 6-benzylaminopurin (BA). The in vitro culture of pistachio seeds in the presence of BA (1.0 - 4.0 mg/l), plus kinetin (Kin, 1.0 mg/l) and naphthalene acetic acid (NAA, 0.25-1.0 mg/l) stimulated varying degree of seed germination and the number of shoots produced. When excised single shoots from these in vitro cultured seeds were subcultured on fresh medium containing high concentration of BA (4.0 mg/l), alongwith Kin and NAA, multiple shoot production was observed. Normal bud growth and shoot elongation were achieved by transferring cultures to the MS medium containing low concentration of the growth regulators BA (1.0 mg/l), plus NAA (0.25 mg/l) and Kin (1.0 mg/l).